First person - Christine Lehner (The Company of Biologists, 2019)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Christine Lehner is first author on 'Tenophages: a novel macrophage-like tendon cell population expressing CX3CL1 and CX3CR1', published in DMM. Christine is a researcher in the lab of Andreas Traweger at Paracelsus Medical University, Salzburg, Austria, investigating the mechanisms leading to tendinopathies.